Subdural empyema : a clinical study - Bok, Arnold Pierre Louis (Division of Neurosurgery, 2017)
Subdural empyema is a relatively rare condition that carries a high mortality if not treated adequately. The experience at Groote Schuur Hospital over 8 years from 1979 to 1986 was reviewed. 47 cases of subdural empyema following on contiguous or distant infection, or where the source was not known, were included in this study. Subdural empyema following cranial operation, head trauma~, or meningitis was excluded. Computer Tomographic scanning facilitated early diagnosis and pinpointed subdural collections, and was used postoperatively, to locate residual subdural pus, which was then drained. The results indicate that an aggressive approach using modern radiological techniques to guide surgical procedures, vastly improves the outcome from subdural empyema. The mortality rate was only 8,5%, while 72,3% of our patients were cured and returned to pre-disease activity. The availability of Computer Tomographic scanning in the management of subdural empyema improves the outcome of patients treated with burrhole drainage and diminishes the need for craniotomy. Rare cases may even be managed with antibiotics only. It remains important to deal with the source of subdural empyema - paranasal in 31, otogenic in 10, osteitis in 2 and not known in 4 of the patients. Anaerobic organisms (28%), which are difficult to culture, and contribute to the high incidence of sterile cultures (32%), play an important role in subdural empyema. Chloramphenicol remains the most useful antibiotic. In the long term only 18,6% of patients had seizures and only 16,3% had focal neurological signs. Complications, especially brain abscess developed in 5 cases where pus was not drained adequately initially, and this contributed to a poorer outcome. Steroid administration did not seem to affect the management of subdural empyema. Repeated surgical drainage and administration of broad spectrum antibiotics remain the mainstays of the treatment of subdural empyema.